Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth

Influence of climate on the seasonality of radial growth of cork oak during a cork production cycle - Costa, Augusta; Pereira, Helena; Oliveira, Ângelo (Ann. For. Sci., 2002)
The radial growth of mature cork oaks (Quercus suber L.) was studied during a 9-year production cycle using monthly dendrometer measurements and cork ring widths. The mean tree radial increase was 5.1 mm yr -1 and the cork increment accounting for 3.8 mm yr -1. The radial growth curves for cork, wood and stem were very similar, showing a decreasing trend along the production cycle. Cork increment was always the largest fraction of tree growth (on average 74%) and showed less inter-annual variations as compared to wood. Tree radial growth presented a clear within-the-year seasonal pattern, extending from March to October, with a maximum in June-July. The overall pattern of monthly growth distribution was similar among the years of the production cycle, but some inter-annual variations occurred with 1-2 month shifts or monthly growth rate decreases, related to climatic factors. Early spring growth was enhanced by winter rain, autumn growth by high summer rain and June increments by high temperatures during this month.
Keywords: climatic fluctuations; cork growth; Cork oak; dendroclimatology; diameter growth